2019
DOI: 10.1111/jocn.14980
|View full text |Cite
|
Sign up to set email alerts
|

“Never in my mind to give up!” A qualitative study of long‐term intensive care patients’ inner strength and willpower—Promoting and challenging aspects

Abstract: Aims and objectives To explore aspects that promote and challenge long‐term ICU patients’ inner strength and willpower. Background Considerable research has been devoted to ICU patients’ experiences; however, research on long‐term ICU patients is limited. Studies in a health‐promoting perspective focusing on long‐term ICU patients’ inner strength and willpower are scarce. Design A qualitative, hermeneutic‐phenomenological approach, using in‐depth interviews. Methods Seventeen long‐term Norwegian ICU patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 38 publications
5
27
0
8
Order By: Relevance
“…43 A wide range of ongoing health impairments was identified, and loss of autonomy was a main aspect. [37][38][39] The views of the GPs identified here is very close to patients' perspectives. The GPs also reported general weakness and low functioning as a main aspect and a very individual apprehension of complaints and impairment.…”
Section: Comparison With Existing Literaturesupporting
confidence: 58%
See 1 more Smart Citation
“…43 A wide range of ongoing health impairments was identified, and loss of autonomy was a main aspect. [37][38][39] The views of the GPs identified here is very close to patients' perspectives. The GPs also reported general weakness and low functioning as a main aspect and a very individual apprehension of complaints and impairment.…”
Section: Comparison With Existing Literaturesupporting
confidence: 58%
“…33 34 As part of this trial, in-depth interviews were held with GPs to explore their experiences with patients discharged from ICU and the intervention. Qualitative research has been conducted with post-ICU patients in detail [37][38][39][40][41][42][43] but, to date, no one had explored in depth the views and experiences of GPs caring for these patients. The aim of this study is to describe GPs' views and experiences of caring for postsepsis patients and of participating a specific outreach training, in order to inform and contribute to applicable future aftercare structures in primary care.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…These approaches for self-reformation are in line with a previous study that psychological adaptation involves effective coping, self-esteem, social integration, and spiritual/existential meaning (Biesecker et al, 2013). A qualitative study showed that intensive care unit patients would explore how to ignite and maintain the spark of life to improve their inner strength and willpower, and the coping skill of learning from past life experience was a useful method (Alexandersen et al, 2019). Therefore, it is important to focus on activation of the individual as a leader in their illness management.…”
Section: Discussionsupporting
confidence: 75%
“…Neglecting of the situational context by individuals is problematic, even though defense mechanisms are a conceptual aspect of adaptation (Beutel, 1985). Assessing the physiological adaptation of individuals is associated with the exploration of the dysfunctional metacognitive beliefs, which is related to anxiety, depression, and perceived quality of life (Alexandersen et al, 2019;Lenzo et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This requires that information from and about the family is transferred between health professionals. Close family members know the patient well and should be acknowledged as essential resources in the care of the patient as they commonly are supportive and represent hope and safety (Alexandersen et al, 2019;Haugdahl et al, 2018). In addition, family members have their own needs.…”
Section: Introductionmentioning
confidence: 99%